1998
DOI: 10.1007/s004210050356
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high-intensity intermittent exercise on the plasma concentrations of glutamine and organic acids

Abstract: Glutamine is an essential substrate for the proper functioning of cells of the immune system. Falls in plasma glutamine concentration after exercise may have deleterious consequences for immune cell function and render the individual more susceptible to infection. The purpose of the present study was to examine changes in plasma glutamine concentration (measured using a validated enzymatic spectrophotometric method) following an acute bout of intermittent high-intensity exercise. Eight well-trained male games … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
1
25
1
10
Order By: Relevance
“…The increased incidence of infection may be due to a prolonged suppression of immune system function. Although duration, rather than intensity of endurance exercise has a greater detrimental impact on the immune system (Robson et al 1999), some aspects of immune function are suppressed following high-intensity intermittent exercise in the laboratory (Pedersen 1991;MacKinnon and Jenkins 1993;Shephard et al 1994;Walsh et al 1998). Bury et al (1998) have also previously found a progressive depression of neutrophil function over a season in professional soccer players, suggesting that games players may have a suppression of the innate immune system similar to that found in endurance athletes.…”
Section: Introductionmentioning
confidence: 98%
“…The increased incidence of infection may be due to a prolonged suppression of immune system function. Although duration, rather than intensity of endurance exercise has a greater detrimental impact on the immune system (Robson et al 1999), some aspects of immune function are suppressed following high-intensity intermittent exercise in the laboratory (Pedersen 1991;MacKinnon and Jenkins 1993;Shephard et al 1994;Walsh et al 1998). Bury et al (1998) have also previously found a progressive depression of neutrophil function over a season in professional soccer players, suggesting that games players may have a suppression of the innate immune system similar to that found in endurance athletes.…”
Section: Introductionmentioning
confidence: 98%
“…Isso pode explicar a ausência de diferença observada no presente trabalho, já que os cavalos testados eram atletas saudáveis e treinados. Muitas observações demonstraram diminuição acentuada nos níveis de glutamina no sangue após exercícios exaustivos, tanto em humanos quanto em animais (WALSH et al, 1998;BASSIT et al, 2000;CUNHA et al, 2004), predispondo assim ao desenvolvimento de doenças do trato respiratório e na sín-drome overtraining (BASSIT et al, 2000;CASTELL, 2003). Talvez, a mensuração da taxa de glutamina/ glutamato fosse um método mais eficiente que apenas a avaliação da glutamina.…”
Section: Discussionunclassified
“…Algumas pesquisas mostraram que, imediatamente após a realização de exercícios considerados como exaustivos, a glutaminemia nem sempre é alterada (DOHM et al, 1981, ROHDE et al, 1996, WALSH et al, 1998a, HISCOCK et al, 2003. Com maior freqüência, uma redução na concentração de glutamina é observada algumas horas (cerca de 2 horas ou mais) após o termino do exercício.…”
Section: Discussionunclassified
“…Com maior freqüência, uma redução na concentração de glutamina é observada algumas horas (cerca de 2 horas ou mais) após o termino do exercício. É provável que esta redução ocorra principalmente em função da elevada utilização de glutamina por células do sistema imune, tais como linfócitos, neutrófilos e macrófagos (KEAST et al, 1995, ROHDE et al, 1996, WALSH et al, 1998a, CURI, 2000, HISCOCK et al, 2003. Entre os fatores estressantes promovidos pelo treinamento prolongado está a produção de amônia plasmática, efeito combinado da desaminação das purinas e catabolismo de aminoácidos dentro das miofibrilas (GRAHAM et al, 1995, NIBO et al, 2005.…”
Section: Discussionunclassified
See 1 more Smart Citation